2009
DOI: 10.1088/0957-4484/20/23/235602
|View full text |Cite
|
Sign up to set email alerts
|

High yield fabrication of fluorescent nanodiamonds

Abstract: A new fabrication method to produce homogeneously fluorescent nanodiamonds with high yields is described. The powder obtained by high energy ball milling of fluorescent high pressure, high temperature diamond microcrystals was converted in a pure concentrated aqueous colloidal dispersion of highly crystalline ultrasmall nanoparticles with a mean size less than or equal to 10 nm. The whole fabrication yield of colloidal quasi-spherical nanodiamonds was several orders of magnitude higher than those previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
247
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(258 citation statements)
references
References 66 publications
5
247
0
6
Order By: Relevance
“…3a). This result reproduced previous reports on NV luminescence in nanodiamonds 4,5,12,14 . However, in free space, discrete 5-nm nanodiamonds containing an NV centre revealed a new luminescence intermittency pattern, for which the effect of the nanodiamond surface state (as in the aggregated or polymer-embedded state) warrants further study.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…3a). This result reproduced previous reports on NV luminescence in nanodiamonds 4,5,12,14 . However, in free space, discrete 5-nm nanodiamonds containing an NV centre revealed a new luminescence intermittency pattern, for which the effect of the nanodiamond surface state (as in the aggregated or polymer-embedded state) warrants further study.…”
supporting
confidence: 92%
“…1b), and their spectra (Fig. 1d) were consistent with those reported for NVs in nanodiamonds 6,14 . Furthermore, the second-order correlation function 1 g (2) (t) (see Methods) confirmed that the emission originated from a single centre (Fig.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…In the nanodiamond-based NSOM probe [9], the optical behavior originates from the point-like transition dipole associated with the radiative transition of the NV colorcenter. We here neglect the finite extension of the host nanocrystal since current trends in nanodiamond processing indicate that it can be diminished down to a few nms only [19,20]. Therefore, we expect the point-like model outlined above to apply to this tip and we will indeed describe the nanodiamond-based tip as a single point-like dipole.…”
Section: Near-field Optical Model Of the Single-photon Tipmentioning
confidence: 99%